Self-consolidating hybrid fiber reinforced concrete: Development, properties and composite behavior. (1st February 2016) - Jen, Gabriel; Trono, William; Ostertag, Claudia P.
Highlights: A self-consolidating hybrid fiber reinforced concrete composite was developed. The composite exhibits high workability and deflection hardening behavior. Fibers ensure ductile response and internal confinement in compression. Reinforced composites tested in tension exhibit tension stiffening behavior. Abstract: The workability of an existing Hybrid Fiber-Reinforced Concrete (HyFRC) composite is improved though the incorporation of concepts from the field of Self-Consolidating Concrete (SCC). The resulting composite, achieved through a described parametric study, allows for easier placement within areas of high reinforcement congestion while maintaining the desired mechanical performance benefits inherent to high performance hybrid fiber-reinforced concrete composites. Retention of the strengthening and ductility enhancement, characteristic of the original HyFRC, is gauged by material response to direct tension and four point bending tests. The designated goal of the SC-HyFRC mix is to provide an optimal structural material for construction in which concrete might be expected to face tension, compression and bending as part of a common service load and must be designed to withstand high levels of deformation under maximum credible earthquake or similar design scenarios. The ductility response of Self Consolidating Hybrid Fiber Reinforced Concrete (SC-HyFRC) to severe loading is then investigated through a comparison with conventional concrete by conducting reinforced compression and tensile tests. In both scenarios the presence of hybrid fiber reinforcement is shown to provide an improvement to the phenomena of internal confinement and tension stiffening, for compression and tension loading respectively, which allow for a significantly improved post cracking response.